Extraordinary therapeutic effect of PSMA radioligand therapy in treatment-refractory progressive metastatic prostate cancer with the transketolase inhibitor benfo-oxythiamine as a radiosensitizer—A case report - Kramer, Carsten S.; Zhang, Jingjing; Baum, Richard P. (Frontiers in Medicine, 2024)
Herein we report, for the first time, the therapeutic response of a prostate cancer patient with the thiamine antagonist benfo-oxythiamine (B-OT) added to prostate-specific membrane antigen(PSMA)targeted radioligand therapy (PRLT). The patient was initially diagnosed as pT3b pN0 (0/7) M0 L0 V0 R0 G3, Gleason score 5+5=10, with an initial prostate-specific antigen (PSA) level of 4.05 ng/ml).Shortly after radical prostatectomy, 68 Ga-PSMA positron emission tomography/computed tomography (PET/CT) revealed PSMA-positive lymph node metastases. Despite treatment with androgen deprivation therapy, external beam radiation therapy, palliative chemotherapy, and five cycles of PRLT ( 177 Lu-PRLT or TANDEM-PRLT respectively), the patient experienced progression in PSA levels as well as in PSMA PET/CT. Due to the intense PSMA expression, 177 Lu-PRLT with 177 Lu-PSMA-I&T was resumed for another 4 cycles (cycles 6 th to 9 th ) and the patient was additionally treated with the thiamine antagonist benfo-oxythiamine. It was hypothesized that B-OT acts as a radiosensitizer by interfering with the repair of damaged DNA. B-OT-PRLT was well tolerated and no substantial changes in laboratory results were observed. Additionally, the patient reported significant improvement in clinical symptoms. Post-treatment 177 Lu-PSMA single-photon computed tomography (SPECT)/CT after the 7 th cycle (and after 2 cycles of B-OT-PRLT) revealed regression of metastases compared to the post-treatment SPECT/CT after the 6 th cycle. Before the 8 th cycle, PSMA PET/CT showed a mixed response following prior uncontrollable cancer progression. Moreover, the PSA level showed a significant decline after one cycle of B-OT-PRLT. Although the patient had experienced massive progression before the first cycle of B-OT-PRLT, he survived for an additional 12 months. This case supports the hypothesis that B-OT-PRLT could overcome radiation resistance in prostate cancer patients who do not initially respond to 177 Lu-or 225 Ac-PRLT.